1984
DOI: 10.1007/bf01658365
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal therapy in anaplastic giant cell thyroid carcinoma

Abstract: A therapy aiming at pre. and postoperative radiotherapy with concomitant chemotherapy has been used in 19 patients with anaplastic giant cell carcinoma of the thyroid gland. Radiotherapy was administered twice daily, 5 days a week; the cytostatic drugs employed were bleomycin, cyclophosphamide, and 5-fluorouracil. Patients with advanced disease (distant metastases and/or vocal cord paralysis, n = 9) had a median survival time from diagnosis of 7 months, while patients with less advanced disease survived on ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…However, most patients promptly developed distant metastases and died from tumor-related causes. Other authors found similar results with combined radiochemotherapy [25,26].…”
Section: Combined Therapeutic Modalitysupporting
confidence: 63%
“…However, most patients promptly developed distant metastases and died from tumor-related causes. Other authors found similar results with combined radiochemotherapy [25,26].…”
Section: Combined Therapeutic Modalitysupporting
confidence: 63%
“…In previous studies by Tennvall et al and Werner et al, death from local failure was seen in 36% and 24% of patients, respectively. These studies used twice daily treatment schedules of varying doses and chemotherapy regimens [ 11 , 21 ]. In our study, death attributed to local failure was seen in 18% of patients, though the patients who developed local failure were inoperable at the time of diagnosis or only received a partial resection or biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] However, to our knowledge, few published data have shown any significant survival benefit from multimodal therapy.…”
Section: Discussionmentioning
confidence: 99%